Azzalaazilu / ??????? - Heiligman, Deborah (New York : Scholastic, 2006)
Text and photographs describe earthquakes and the damage they cause.
Text in Arabic.
Includes index.
3-6
Translation of: Earthquakes.
Title supplied by OCLC WorldCat.
Keywords: Earthquakes; Arabic language materials; Earthquakes; Arabic language